Pemungutan kurkumin dari kunyit (Curcuma domestica val.) dan pemakaiannya sebagai indikator analisis volumetri - Ratna Sri Harjanti (Jurnal Rekayasa Proses, 2008)
Volumetric analysis is one of quantitative analysis methods; a very important method used in determining the concentration of substances in solution. The success of this analysis was determined by the existence of an appropriate indicator that can show the exact end-point of titration. Curcumin, a natural dye contained in the plant root of turmeric (Curcuma domestica val.) was able to function as an indicator for the color change from light yellow brown to brown at pH around 4.5 to 9.9. Curcumin is extracted from the tuber which result is called oleoresin extraction. In the case of extraction of oleoresin, the role of solvent, extraction duration, temperature, and the fineness of particles is very important. In the present work curcumin pigment was extracted from turmeric paste in ethanol as solvent at varying operating conditions; i.e temperature, duration of extraction, and particle size of turmeric powder. The extract was further distilled and weighed. The curcumin obtained at optimum conditions was then determined using a TLC Scanner. The use of curcumin as an indicator in volumetric analysis was done by mean of titration using a few acid-basic samples. The results were compared with results from titrations using phenolphthalein (pp) and methyl-orange (mo) as indicators. The results showed that the optimum condition of curcumin extraction were at a temperature of 70°C for 120 minutes with a turmeric particle size of 100 mesh. The curcumin produced had a relatively high concentration of 5.158 mg/mL. In order to use it as an indicator for the end-point of volumetric analysis, the curcumin should be diluted to obtain 5% solution and use as much as 4 drops of the solution for the titration.